PERILAKU LESBIAN, GAY, BISEKSUAL, DAN TRANSGENDER (LGBT) PERSPEKTIF USHUL FIKIH MU‘TAZILAH: TELAAH KITAB AL-MU‘TAMAD FĪ UṢŪL AL-FIQH - Chairul Lutfi; Abdurahman Abdurahman; Bintan Dzumirroh Ariny; Akhmad Farroh Hasan (STAI ALHIKMAH Jakarta, 2025)
AbstractThis study aims to examine how the concepts within Mu‘tazilite uṣūl al-fiqh, particularly as formulated in Kitāb al-Mu‘tamad fī Uṣūl al-Fiqh by Abū al-Ḥusain al-Baṣrī, can offer a theoretical response to contemporary issues concerning LGBT (Lesbian, Gay, Bisexual, and Transgender) behavior. The study employs a qualitative method based on library research, using a thematic analysis approach to explore normative ideas in the aforementioned text. The primary focus is directed toward the exploration of two foundational uṣūl principles in Mu‘tazilite thought: the classification of human acts (al-Af‘āl) and the method of legal analogy (al-Qiyās al-Shar‘ī), both of which are grounded in the principles of rationality and justice. The findings suggest that LGBT behavior, within the framework of al-Mu‘tamad, can be categorized under the spectrum of qabīḥ (morally reprehensible) actions. Nevertheless, the rationalist nature of the Mu‘tazilite approach opens up possibilities for a contextual re-evaluation of this legal classification, taking into account modern developments in social norms and human rights discourse. This study does not intend to render a rigid legal verdict but rather proposes a reflective space for developing a more inclusive and adaptive fiqh. Accordingly, the main contribution of this research lies in strengthening the discourse of uṣūl al-fiqh based on reason and universal values, thereby creating a bridge between classical texts and contemporary socio-religious challenges.AbstrakPenelitian ini bertujuan untuk menelaah bagaimana konsep-konsep dalam ushul fikih Mu‘tazilah, khususnya sebagaimana dirumuskan dalam Kitab al-Mu‘tamad fī Uṣūl al-Fiqh karya Abū al-Ḥusain al-Baṣrī, dapat memberikan respons teoretis terhadap problematika kontemporer mengenai perilaku LGBT (Lesbian, Gay, Biseksual, dan Transgender). Studi ini menggunakan metode kualitatif berbasis studi kepustakaan dengan pendekatan analisis tematik terhadap gagasan normatif dalam kitab tersebut. Fokus utama diarahkan pada eksplorasi dua perangkat ushul utama dalam pemikiran Mu‘tazilah, yaitu klasifikasi tindakan (al-Af‘āl) dan metode analogi hukum (al-Qiyās al-Syar‘ī), yang keduanya dibangun di atas asas rasionalitas dan keadilan. Hasil kajian menunjukkan bahwa perilaku LGBT dalam kerangka al-Mu‘tamad dapat dikategorikan ke dalam spektrum perbuatan qabīḥ (tercela). Namun demikian, sifat rasionalistik dari pendekatan Mu‘tazilah membuka peluang untuk mempertimbangkan ulang kategori hukum tersebut secara lebih kontekstual, dengan memperhatikan perkembangan sosial dan wacana hak asasi manusia masa kini. Penelitian ini tidak bertujuan untuk memberikan vonis hukum yang kaku, melainkan mengusulkan ruang reflektif bagi pengembangan fikih yang lebih inklusif dan adaptif. Dengan demikian, kontribusi utama studi ini terletak pada penguatan diskursus ushul fikih berbasis nalar dan nilai-nilai universal, yang dapat menjembatani teks klasik dengan tantangan sosial keagamaan modern.